Understanding the Role of Stigma and Misconceptions in the Experience of Epilepsy in India: Findings From a Mixed-Methods Study - Gosain, Kritika; Samanta, Tannistha (Frontiers in Sociology, 2022)
It is surprising that although 12 million people in India suffer from epilepsy this remains a thoroughly under-researched area in the sociology of health and practice. We address this intellectual and policy neglect by reviewing the social, psychological and legal challenges governing the lives of people living with epilepsy (PWE) by paying particular attention to negotiations in arranged marriages and employment. Building on the sociological study of stigma, critical race theory and cultural models of health and suffering, this study utilized a combination of (online) survey data (N=100) and in-depth qualitative interviews (N=10) with PWE and their families. The online survey was administered to map the level of awareness about epilepsy and its clinical management among the general population, whereas the in-depth interviews were conducted to understand the experience, self-perception and everyday struggles of those diagnosed with the condition. Findings from the survey on non-PWE suggest a general lack of awareness and fearful misconceptions around epilepsy related seizures. In-depth interviews with PWEs revealed concealment (of the illness) as a dominant coping strategy to attenuate the social alienation and rejection associated with epilepsy. Further, PWE participants reported persistent discrimination, harassment and prejudiced understanding of diminished cognitive capacities at workplaces as a result of cultural myths and popular representations of epilepsy-related seizures. The study also demonstrated the significance of institutional support groups in assisting PWE to cope with symbolic violence and forge solidarities. We conclude with reflections on the ethical dilemmas faced by medical practitioners while dealing with social-medical interventions of epilepsy treatment. Overall, results from this study undergird the significance to revisit the social-moral as well as legal frameworks that persistently restrict opportunities for PWE in India. In an attempt to reimagine inclusive futures regardless of disease, disability and affliction, we attempt to move beyond the biomedical gaze and instead privilege stories of individual personhood, struggles and aspirations.